GOVERNMENT INTERVENTION IN THE ECONOMY AND CRISIS RESILIENCE - ISMAILOVA, Fidan (CENTRAL ASIA AND THE CAUCASUS, 2017)
The author utilizes the results of the latest global crisis to explore the methodology for assessing the correlation between the level of government intervention in the economy and its resilience to crises. The analysis is based on a modified version of the Index of Leftness (Rightness) of Economy, developed by Prof. Nazim Muzaffarli, along with the Cumulative Loss Index. The examination of this correlation, conducted for 57 countries, revealed that nations with a higher degree of government intervention in the economy prior to the global crisis exhibited a weaker defensive response to the crisis and greater cumulative losses. This indicates that government intervention in capital flows, price formation, and licensing significantly undermines the economic entities’ resilience or "immunity" to crises.